PERANAN KOMUNIKASI INSTITUSI BUNDOKANDUANG DALAM MELESTARIKAN NILAI-NILAI BUDAYA MINANGKABAU DI NAGARI ALAHAN PANJANG KABUPATEN SOLOK SUMATERA BARAT - Nurul Asra Hadi; Noor Efni Salam (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Bundokanduang an institution or agency of indigenous women Minangkabau interpreted as true mother whose maternal instincts and leadership and ‘women's role as an institution that plays a role in preserving the cultural values of Minangkabau. And this study aims to determine the role of communication Bundokanduang institutions in preserving the cultural values of Minangkabau.The method used in this study is a qualitative method approach symbolic interaction. Data were collected through observation, interviews, and documentation. Informants contained in this research consisted of seven people is determined by purposive sampling.Role of Information Bundokanduang institutions have in the preservation of cultural values of Minangkabau, through programs run Bundokanduang role information. divided into three programs, namely in the areas of organization, education, and the field of customary law, in addition Bundokanduang also provides preservation of cultural values in the form of nature and daily behavior. Deciding role Bundokanduang Nagari Alahan Panjang, was seen on the termination respond to reality in society, and policies are being made to use the inheritance.Keywords: Bundokanduang, The Role of Communication, Culture Minangkabau